Effect of Longevity Risk on Retirement Planning - Lewat, Joseph (American Journal of Statistics and Actuarial Sciences, 2024)
Purpose: The aim of the study was to assess the effect of longevity risk on retirement planning. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that failing to account for longevity risk can lead to insufficient income in the later stages of retirement, forcing retirees to reduce their standard of living or rely on external support. Consequently, retirement planners and individuals are advised to incorporate longevity risk into their planning by considering annuities, adjusting withdrawal rates, and diversifying investment portfolios to ensure a stable income stream throughout retirement. Financial education and tools to estimate life expectancy are also essential in helping individuals make informed decisions about their retirement savings and disbursement strategies, ultimately leading to more secure and sustainable retirement outcomes. Implications to Theory, Practice and Policy: Life-cycle hypothesis (LCH), prospect theory and modern portfolio theory may be used to anchor future studies on assessing the effect of longevity risk on retirement planning. Implementing widespread financial literacy initiatives can empower individuals to make informed decisions about retirement planning. Governments should introduce policies that incentivize higher savings rates, such as tax benefits for retirement contributions and automatic enrollment in retirement plans.